THE INFLUENCE OF DIGITAL LITERACY AND INNOVATION ON ENTREPRENEURIAL INTEREST IN VOCATIONAL SCHOOL STUDENTS IN DEPOK CITY - Hugo Aries Suprapto (Bajang Institute, 2021)
The aim of this research is to determine the influence of digital literacy on interest in entrepreneurship, and to determine the influence of innovation on interest in entrepreneurship. The method uses quantitative, with Autocorrelation Test assumptions, Multicollinearity Test and Multiple Regression Analysis. Data was taken through filling out questionnaires, interviews and documentation. The respondents were 55 vocational school students in the marketing study program. The results of the research are that digital literacy and innovation have an influence of 41.5%, while the rest is influenced by other factors. Students and teachers should start carrying out entrepreneurial activities together when they are in class X, so that they gain more real insight and views about the ins and outs of entrepreneurship.